Pengaruh Ukuran, Profitabilitas, dan Kebijakan Dividen Terhadap Nilai Perusahaan Manufaktur di BEI - Umi Fadhilatun Nikmah (Commodities, Journal of Economic and Business, 2024)
This research was conducted with the aim to determine the effect of company size, profitability, and dividend policy partially and simultaneously on firm value in the cement sub-sector and the ceramics, porcelain, and glass sub-sectors listed on the Indonesia Stock Exchange in 2012-2017. The independent variable used in this study is company size, profitability that is proxied by ROE (return on equity), and dividend policy that is proxied by the DPR (dividend payout ratio). The dependent variable used in this study is company value with the PBV ratio indicator (price to book value). This study uses secondary data with a sample of 5 companies. Data analysis was performed with multiple linear regression with the help of SPPS version 16. The results showed that partially the size of the company did not have a positive and significant effect on firm value, profitability and dividend policy partially had a positive and significant effect on firm value. Simultaneously the size of the company, profitability, and dividend policy affect the value of the company. Predictive ability of the three variables on company value obtained by R square value of 0.740 or 74% can be concluded that the variable firm size, profitability, and dividend policy can explain the variable value of the company and the remaining 26% is explained by other factors outside of this study.